The effect of garlic (Allium Sativum) powder on growing sprague dawley rats fed a high-fat high-fructose diet - Ngoetsana, Tshepiso (My University, 2019)
Obesogenic [high- fat high- fructose (HFHF)] diets increase the prevalence of obesity and associated metabolic derangements (MD) in children. Conventional medicaments used to manage obesity besides being costly elicit side effects hence communities rely on ethnomedicines. Garlic, an ethnomedicine, has antioxidant, hypoglycaemic and hypolipidaemic properties. This study evaluated the prophylactic potential of garlic powder (GP) in growing Sprague-Dawley (SD) rats against diet-induced MD. Eighty 21-day old SD rats were randomly allocated to and administered treatment regimens: group 1- rat chow (SRC) + drinking water + gelatine cube (PGC); group 2- SRC with 2% beef tallow and 20% fructose solution (HFHF) + PGC; group 3- HFHF + fenofibrate (100mg/kg bwt/day) and group 4- HFHF + GP (100mg/kg bwt/day) for 8 weeks. Growth, glucose tolerance, metabolic substrate content, viscera morphometry, and general health profile were determined. The HFHF diet, fenofibrate, and GP did not affect (P > 0.05) growth performance. The haematocrit of males was decreased (P< 0.05) by the HFHF diet. The HFHF diet did not affect (P > 0.05) the area under the curve (AUC) of the oral glucose tolerance test. Fenofibrate and GP did not affect (P > 0.05) the AUC of female rats but increased the AUC (P < 0.05) of male rats. In both sexes, treatment regimens had no effect (P > 0.05) on plasma insulin and cholesterol concentration and HOMA-IR. In females, fenofibrate increased (P < 0.05) blood glucose concentration compared to that of counterparts fed the HFHF diet. The HFHF diet increased (P < 0.05) plasma triglyceride concentration in both sexes but did not affect (P > 0.05) liver lipid content of females, however it decreased (P < 0.05) that of males. The HFHF diet-induced hypertriglyceridaemia was prevented by fenofibrate in males. Garlic powder and fenofibrate increased (P < 0.05) the liver lipid content in both sexes. In females, the HFHF diet caused hepatic steatosis and inflammation (P < 0.05). Garlic powder and fenofibrate protected against the HFHF diet-induced hepatic steatosis and inflammation. Fenofibrate increased (P < 0.05) liver mass in both sexes but increased (P < 0.05) kidney mass of males. The HFHF diet increased (P < 0.05) visceral and epididymal adiposity in the rats. Garlic powder and fenofibrate protected the females against the visceral adiposity. The diet-induced epididymal adiposity was prevented by garlic powder. The HFHF diet decreased BUN (P < 0.05) and fenofibrate increased (P < 0.05) the BUN: creatinine ratio. The HFHF showed sexual dimorphism in eliciting metabolic derangements. In both sexes, GP protected against the HFHF diet-induced metabolic derangements in a sexually dimorphic manner. In growing children, garlic powder and fenofibrate can potentially be used to protect against some components of the HFHF diet-induced MD but should be used with caution as they might cause adverse health outcomes.
A Dissertation submitted to the Faculty of Health Sciences, University of Witwatersrand, Johannesburg, in fulfilment of the requirements for the degree of Master of Science in Medicine. Johannesburg, 2019